RANCANG BANGUN SISTEM INFORMASI DENGAN MENGGUNAKAN METODE TOPSIS DAN SAW DALAM MEMBERIKAN REWARD PELANGGAN (Studi Kasus: PT BOLDE MAKMUR INDONESIA) - Fachmi Fahrezi; Teti Desyani (CV. Multi Kreasi Media, 2022)
In the world of sales industry, competition is a very natural thing. The number of businesses with the same type of goods and items makes an owner or business owner have to rack his brain to have the right strategy in increasing customer purchasing power and reaping a profit for the company. This study aims to provide a solution when the company is facing a declining trend in sales, so as to minimize the decline in the purchasing power of customers in the company. Among them are implementing algorithms in computer science to create a decision support system for giving rewards to customers at PT Bolde Makmur Indonesia. And a special flow is made for staff and cashiers to make it easier to give rewards to customers. In its implementation, the reward application system uses the PHP programming language, the codeigniter framework, and data storage using MySQL Workbench. In this study the method used is TOPSIS and SAW methods. Where the assessment criteria are the size of the transaction, the number of orders, the number of quantities. From the results of the comparison of the two methods, it is obtained that calculations performed by the TOPSIS method are better than the SAW method.